Role of the mevalonate pathway in specific CpG site demethylation on AGEs-induced MMP9 expression and activation in keratinocytes. (15th August 2015) - Lu, Wan; Li, Jin; Ren, Meng; Zeng, Yinjuan; Zhu, Pin; Lin, Li; Lin, Diaozhu; Hao, Shaoyun; Gao, Qi; Liang, Junqiang; Yan, Li; Yang, Chuan
Highlights: The mevalonate pathway was involved in AGE-enhanced MMP9 expression. The CpG site at -562 site was largely demethylated with AGE–BSA treatment. The mevalonate pathway for DNA demethylation was a new found. The contraction of demethylation would be useful in treatment of diabetic foot. Abstract: Background: Advanced glycation end products (AGEs) played an important role for the development of diabetic foot. In the present study we tried to show the mevalonate pathway and the key demethylation site(s) in the MMP-9 cis-promoter to the component of MMP-9 by AGEs in keratinocyte. Method: Human keratinocyte cell line (HaCaT) cells were exposed to AGE–BSA. The plasmid construction and site-directed mutagenesis, dual-luciferase reporter assays, immunoblot, zymography, pull down, bisulfite sequencing PCR analysis and Western blotting were applied. Results: The AGE–BSA could increase and more activate the MMP9 in keratinocyte. The RhoA and ROCK1 also could be activated. These affects were blocked by the simvastatin. Meanwhile, the CpG site at −562 site was largely demethylated with AGE–BSA treatment. The cis-promoter sequences with −562 bp site methylated had a lower activity change, which had a highest expression activity and was decreased by simvastatin. Moreover, site-directed mutagenesis of CpG site (−562 bp) in the recombinant plasmid pCpGL-571 brought more reduction in activity, and the activity of methylated mutation pCpGL-571 remains decreased. Conclusion: The cis-promoter regions of MMP9 would be methylated by AGE–BSA in keratinocyte through the mevalonate pathway, especially the −562 bp site.